Strength of structural elements - Zyczkowski, Micha (Studies in applied mechanics ;, 1991)
This volume describes engineering applications of the mechanics of deformable bodies and the elasticity theory relevant to them. It is concerned mainly with one-dimensional problems, which arise because either one of the dimensions of a body is much greater than the remaining two or the functions of two or three variables may be reduced to one variable. Problems of this type are of twofold importance. Firstly, many engineering problems can be described with sufficient accuracy just in this way. Secondly, unidimensional problems with known analytical solutions may serve either for testing numerical methods or for the analysis of fundamental concepts and phenomena, whose physical nature in three-dimensional approach might be obscured by the analytical-numerical aspect. The authors have confined themselves for the most part to the analysis of elastic behaviour of structures; however some attention is also given to elastic problems. A deterministic approach has been applied throughout the book. It will serve as a springboard for further work with stochastic approaches which are being increasingly used in engineering practice today.